Functional characterization of a novel de novo CACNA1C pathogenic variant in a patient with neurodevelopmental disorder - Stringer, Robin N; Tang, Xuechen; Jurkovicova-Tarabova, Bohumila; Murphy, Mary; Liedl, Klaus R; Weiss, Norbert (Molecular brain, 2025)
Mutations in CACNA1C, the gene encoding Cav1.2 voltage-gated calcium channels, are associated with a spectrum of disorders, including Timothy syndrome and other neurodevelopmental and cardiac conditions. In this study, we report a child with a de novo heterozygous missense variant (c.1973T > C; L658P) in CACNA1C, presenting with refractory epilepsy, global developmental delay, hypotonia, and multiple systemic abnormalities, but without overt cardiac dysfunction. Electrophysiological analysis of the recombinant Cav1.2 L658P variant revealed profound gating alterations, most notably a significant hyperpolarizing shift in the voltage dependence of activation and inactivation. Additionally, molecular modeling suggested that the L658P mutation disrupts interactions within the IIS5 transmembrane segment, reducing the energy barrier for state transitions and facilitating channel opening at more negative voltages. These findings establish L658P as a pathogenic CACNA1C variant primarily associated with severe neurological dysfunction and expands the phenotypic spectrum of CACNA1C-related disorders.
Keywords: vápníkové kanály - typ L; L658P; Ion Channel Gating; Calcium channel; Mutation, Missense; Male; neurovývojové poruchy; mutace; missense mutace; HEK293 buňky; Electrophysiology; Child; gating iontového kanálu; dítě; Amino Acid Sequence; HEK293 Cells; mužské pohlaví; molekulární modely; Calcium Channels, L-Type; Neurodevelopmental Disorders; Models, Molecular; lidé; ženské pohlaví; CACNA1C; Humans; Cav1.2; sekvence aminokyselin; Channelopathies; Mutation; Female